2016
DOI: 10.1016/j.ajhg.2016.06.035
|View full text |Cite
|
Sign up to set email alerts
|

De Novo Truncating Variants in SON Cause Intellectual Disability, Congenital Malformations, and Failure to Thrive

Abstract: SON is a key component of the spliceosomal complex and a critical mediator of constitutive and alternative splicing. Additionally, SON has been shown to influence cell-cycle progression, genomic integrity, and maintenance of pluripotency in stem cell populations. The clear functional relevance of SON in coordinating essential cellular processes and its presence in diverse human tissues suggests that intact SON might be crucial for normal growth and development. However, the phenotypic effects of deleterious ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
108
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(115 citation statements)
references
References 38 publications
(61 reference statements)
6
108
0
Order By: Relevance
“…3a). The former is derived from a SON mutation reported by Kim et al [1], and the latter is from the most prevalent mutation found in ZTTK syndrome [1,3,4]. The effective production of hSONr, hSONm1, and hSONm2 in HEK293 cells in the presence of shRNA#1 was con rmed (Fig.…”
Section: Resultsmentioning
confidence: 55%
See 4 more Smart Citations
“…3a). The former is derived from a SON mutation reported by Kim et al [1], and the latter is from the most prevalent mutation found in ZTTK syndrome [1,3,4]. The effective production of hSONr, hSONm1, and hSONm2 in HEK293 cells in the presence of shRNA#1 was con rmed (Fig.…”
Section: Resultsmentioning
confidence: 55%
“…Instead, other functions, such as transcriptional regulation, are more relevant to neural pathology since SON interacts with more than a thousand of genes via its DNA-binding region and is involved in the transcriptional repression of many target genes [9]. This is supported by the fact that rare non-truncating mutations, i.e., missense mutations [4] and an in-frame deletion [1], identi ed in ZTTK syndrome patients, are located exclusively in and around the genomic region that encodes the DNA-binding region (Table 1). However, there is a possibility that hSONm2 in uences SON-mediated RNA splicing because of its structural similarity to SON E, a physiological isoform of SON.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations